VALUES OF THE MEDICINAL BATH PLACE ENVIRONMENT: THE IMPORTANCE OF MEDICINAL BATH PLACE CHARACTERISTICS AMONG HUNGARIANS - Hojcska, Ágnes Erzsébet; Szabó, Zoltán; Bujdoso, Zoltán (Polish Journal of Natural Sciences, 2024)
The main topic of our research is the examination of the environmental values of Hungarian medicinal bath place from the demand side, which can significantly contribute to the preservation of people’s health and the improvement of their quality of life. The actuality of our research is due to the fact that in our society, people pay more and more attention to health presevation and their personal well-being. The water usually attracts people, so the medicinal bath place environment appears as a defining element of the offer among tourists. The main goal of our research is to map out, with the help of consumer attitudes and preferences, the expectations of tourists regarding the characteristics of medicinal bath place. To achieve the goal of our research, we conducted primary research and a questionnaire survey. Data collected among the Hungarian middle-aged middle class (n = 200) were processed with univariate descriptive statistics and bivariate analyses. In the course of our research, we came to the results that the Hungarian middle-aged middle class clearly detects the medicinal bath place characteristics, and that the main medicinal bath place characteristics can be divided into characteristically different ways of thinking. In the opinion of the respondents, among the features of the spa, the silence and tranquility, the quality of the accommodation, the beautiful environment, the wide range of treatments, as well as the quality of the gastronomy and medicinal care significantly contribute to a successful stay in a medicinal bath place. We also determined the three main ways of thinking of spa visitors: environment-oriented way of thinking, medicinal-oriented way of thinking, culture-oriented way of thinking, which is most characteristic of a satisfied guests.